LEGAL FRAMEWORK OF HIGHER EDUCATION IN RUSSIA NEEDS RECONFIGURATION - V. S. Senashenko (Высшее образование в России)
This paper is a comment on the article of S.V. Korshunov “The System of Standardization of Education in the Russian Federation Celebrates a Quarter of a Century “ published in the previous issue of the journal. The paper highlights a wide range of problems connected with Russian higher education system functioning, such as, education management, retrospective review of educational standards, the current state of Federal state educational standards of higher education, the modular structure of educational programs, academic freedoms of Universities in determining the content of higher education. The regulatory documents that specify the features of the integrated system of higher education should have a framework character. At the same time the educational process should be organized so that the problem of full staffing of all the branches of national economy could be solved. The analysis of the regulatory and legal provisions of national higher education shows that it’s time to shift from the educational standards of higher education in their current form as they are not relevant the established educational reality. First and foremost, the current system of Federal state educational standards cannot solve the vital problem of coupling higher school with the Labor sphere, that is why it needs a thorough reconfiguration.